Breast cancer patients' experience with receiving pathogenic germline genetic results: single center experience in Oman - Balushi, Amira (Department of Pathology, 2025)
Introduction: In Oman, little is known about breast cancer patients' experiences of receiving pathogenic germline genetic results. Receiving a positive germline genetic result can have a wide range of emotional and practical effects on breast cancer patients. This study explored the lived experiences of Omani women navigating a positive pathogenic germline genetic test result for hereditary breast cancer. Driven by the increasing prevalence of genetic testing and limited research on its psychosocial impact within this specific cultural context, the study aimed to understand how Omani women experience and make sense of a positive genetic test result. Methods: This is a qualitative study based on an interpretive phenomenological approach. Semi structured interviews were conducted with nine Omani women who had received a positive germline genetic result for breast cancer predisposition gene. Thematic analysis was employed to identify key themes emerging from these women's experiences. Result and Discussion: Four themes emerged from the thematic analysis in this study. These included “Cancer journey”, “Genetic testing motivation and expectations”, “Receiving the positive result”, and “Adapting to hereditary breast cancer diagnosis”. The findings revealed the complex and multifaceted experience of breast cancer women with receiving positive germline genetic result. The perceived causation of their breast cancer, such as stress and pre-existing cultural beliefs, as well as their lived experiences during the cancer diagnosis and treatment, all influenced these women's response and understanding of their genetic test result. Emotional responses varied, ranging from anxiety and fear to relief and empowerment, highlighting the individual nature of this experience. Coping strategies were active coping such as leaving the matter to God's hand, increased surveillance and risk-reducing surgeries, engagement coping with family and friends for support, and meaning-focused coping, often grounded in religious and spiritual beliefs. Family dynamics and cultural norms played a crucial role in disclosure practices, with concerns about protecting family members from psychological stress having influenced their decisions about information sharing. x Conclusion: This research contributes valuable insights into the lived experiences of Omani women with hereditary breast cancer, highlighting the need for culturally sensitive and individualised support throughout the testing and decision-making process. The findings have implications for healthcare professionals, genetic counsellors, and policymakers, emphasizing the importance of providing comprehensive support that addresses the emotional, social, and cultural dimensions of hereditary cancer risk.